Algebra 2

posted by .

For positive x and y, which expression is equivalent to (x^1/2-y^1/2)^2?

a. x-y
b. x+2sqrt(xy)+y
c. x-2sqrt(xy)+y

I need all of the steps to get to the right answer.
Thanks

  • Algebra 2 -

    (√x - √y)^2
    = x - 2√(xy) + y

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calc check: curve length

    Find the length of the curve y=(1/(x^2)) from ( 1, 1 ) to ( 2, 1/4 ) [set up the problem only, don't integrate/evaluate] this is what i did.. let me know asap if i did it right.. y = (1/(x^2)) dy/dx = (-2/(x^3)) L = integral from a …
  2. Math

    A series circuit contains a resistor with R = 24 , an inductor with L = 2 H, a capacitor with C = 0.005 F, and a generator producing a voltage of E(t) = 12 sin(10t). The initial charge is Q = 0.001 C and the initial current is 0. Find …
  3. Algebra

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  4. Algebra - sqrts

    Square roots. Woohoo. Want to check some work I did. 1. Perform indicated operations 3sqrt[3]+2sqrt[27]-sqrt[12] 3sqrt[3]+2sqrt[3*9]-sqrt[2*6] 3sqrt[3]+3*2sqrt[3]-2sqrt[3] 3sqrt+6sqrt[3]-2sqrt[3] = 7sqrt[3] 2.Simplify sqrt[49x^12y^4z^8] …
  5. multiplying exponents

    what is X^2sqrt(X) Is it X^(2+0.5)=X^(5/2) because if it is then why don't my numbers match?
  6. algebra homework

    2sqrt x+1-1=6-x I really need some help because I am so lost,so can someone please help me?
  7. Algebra 2 ..

    Solve by completing the square. 5x^2+10x-7=0 My answer: x= -1+ or - 2sqrt.of 10 all over 5
  8. Math

    Rearrange equation to isolate for P to use in a calculator please v=e[(1/cos(pi/2sqrt(P/Pcr)))-1] OR e[(sec(pi/2sqrt(P/Pcr)-1]
  9. Algebra ASAP (Please helpeth this lost soul)

    Simplify (2sqrt(5)+3sqrt(7))^2 ~~~ Can you show the steps. I want to learn how to do it now so I won't have to pester y'all again with my feeble algebra questions :3
  10. math

    to simplify (2sqrt(b)-sqrt(3a))(2sqrt(b)+sqrt(3a)) answer is -3a+4b. how would you get this?

More Similar Questions